2019
DOI: 10.1111/cdep.12345
|View full text |Cite
|
Sign up to set email alerts
|

Love Them and Hate Them: The Developmental Appropriateness of Ambivalence in the Adolescent Sibling Relationship

Abstract: The quality of sibling relationships has important implications for each sibling's development, and not always in the expected ways, because both conflict and intimacy are associated with both positive and negative developmental outcomes. Additionally, these relationship qualities do not occur in isolation since sibling relationships are known as the quintessential love-hate relationship. The ambivalence (i.e., coexistence of positive and negative feelings) siblings experience toward one another during childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Our results indicate that stepsibling conflict should be normalized. Among biological siblings, conflict is recognized as normative, inevitable, developmentally appropriate, and ultimately a sign of closeness (Campione-Barr & Killoren, 2019). Although representations of biological siblings celebrate the ambivalence that is inherent to sibling ties (i.e., high conflict, high warmth, or the "love-hate relationships"; Campione-Barr & Killoren, 2019), stepfamily relationships are often viewed through a binary lens of either harmonious or conflicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that stepsibling conflict should be normalized. Among biological siblings, conflict is recognized as normative, inevitable, developmentally appropriate, and ultimately a sign of closeness (Campione-Barr & Killoren, 2019). Although representations of biological siblings celebrate the ambivalence that is inherent to sibling ties (i.e., high conflict, high warmth, or the "love-hate relationships"; Campione-Barr & Killoren, 2019), stepfamily relationships are often viewed through a binary lens of either harmonious or conflicted.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescent siblings often experience conflict with greater frequency and intensity when there are perceived violations of boundaries regarding personal space or friendships (Campione-Barr & Killoren, 2019;McGuire & Shanahan, 2010). Although sibling conflict can be beneficial for individual and relational development, greater frequency and intensity of conflict are associated with less positive sibling relationships (Campione-Barr & Killoren, 2019).…”
Section: Benefits Of Relational Conflictsmentioning
confidence: 99%
“…Previous research regarding singleton siblings suggest that sibling relationships involve balancing between closeness and conflict (Dirks et al, 2015). As siblings represent a close-field relationship (e.g., relationships that are constrained by genetics, norms, or laws) they can withstand greater negativity than relationships such as friendships (Campione-Barr & Killoren, 2019). Indeed, previous studies found that singletons' and twins' closeness and conflict are not bi-polar opposites, and can coexist (Furman & Buhrmester, 1985;Kim et al, 2006;Loh & Elliott, 1998;N.…”
Section: The Associations Among the Twins' Relationship Dimensionsmentioning
confidence: 99%
“…While intense conflict is predictive of maladjustment, it is also a normative part of sibling relationships (Campione-Barr & Killoren, 2019). Siblings are not chosen, they spend the most time together, and their relationships are characterized by uninhibited affect and behavior.…”
Section: Conflict In Sibling Relationshipsmentioning
confidence: 99%